New microsatellite markers for Dacryodes edulis (Burseraceae), an indigenous fruit tree species from Central Africa - Rimlinger, Aurore; Marie, Lison; Avana-Tientcheu, Marie Louise; Bouka Dipelet, Ulrich G.; Zekraoui, Leila; Cedric, Mariac; Carrière, Stéphanie; Duminil, Jérôme (Springer, 2020)
Microsatellites were designed and characterized in the African fruit tree species Dacryodes edulis (Burseraceae). The fruits are commercialized throughout Central Africa and the species is present in forested environments as well as cultivated systems. The high variability of these markers makes them suitable to investigate the structure of genetic diversity in this important food tree species from Central Africa. From a genomic library obtained by next-generation sequencing, 21 new polymorphic microsatellite loci were developed. Tested on 95 individuals from four populations coming from three countries of the Congo Basin, the microsatellites displayed two to 20 alleles (mean 7.5; expected heterozygosity 0.003 to 0.937, mean 0.666). The transferability of microsatellites was effective for four other Dacryodes species (D. buettneri, D. igaganga, D. osika, D. pubescens). This set of newly developed microsatellite markers will be useful for assessing the genetic diversity and differentiation as well as gene flow patterns of D. edulis in tropical forests from Central Africa.